The effects of work environmental factors on job satisfaction: The mediating role of work motivation - Taghrid S. Suifan (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This paper explores how work motivation mediates the association between work environmental factors and job satisfaction. The data were collected through a questionnaire survey administered to middle and top managers in Jordanian commercial banks. A total of 295 questionnaires were returned out of 500, with a response rate of 59%. Validity and reliability analyses were performed, and direct and indirect effects were tested using structural equation modelling. Work motivation was found to positively and significantly mediate the effects of work environmental factors on job satisfaction. This finding is attributed to work itself and its contextual factors contributing to employees' positive feelings towards their jobs, depending on the effectiveness of their work motivation. This study fills a gap in the literature on how the psychological environment of the workplace affects work environmental factors.
Keywords: M19; 650; work environmental factors; work motivation; job satisfaction; job insecurity; quantitative demands